The Prospect of a Global Ethic on HIV/AIDS: The Religions and the Science–and–Religion Dialogue - Moore, James F. (Zygon, 2003)
This article introduces essays from a 2001 symposium on a global ethic and the issue of the spread of HIV/AIDS. The symposium began with the assumption that we can determine the possibility for such a global ethic if we both explore the potential of an interreligious dialogue and do so in the context of a science–and–religion dialogue. I argue that while the possibilities for a global ethic, in particular addressing the issue of HIV/AIDS, may be debated, the results of this symposium suggest that the dialogue ought to be continued and that there is significant potential in the interfaith dialogue for creating models for both an ethic and specific strategies for action.